Analisis Keamanan Infrastruktur Jaringan Berdasarkan Cyber Kill Chain Framework - Utama Hasiolan Panggabean; Benfano Soewito (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study concentrates on examining the security of network infrastructure using the cyber kill chain framework approach. The research is conducted within a company operating in network security services. In its operations, it offers a Virtual Private Cloud (VPC) containing various crucial information such as applications, internal data, client data, and product demos. Despite the attractive features of cloud computing, there are significant threats as well. Handling attacks cannot be swiftly and efficiently executed, resulting in temporary operational unavailability until the attacks are resolved. This research delves into the security of the company's infrastructure by testing several points of vulnerability exploited by malicious parties. The cyber kill chain framework approach is employed to systematically assess the company's infrastructure. The study reveals that certain issues have been adequately detected; however, security gaps persist, as evidenced by the testing conducted and the inadequate response from the company's security systems.